Correlational analysis of challenging behaviours. - Whitaker S; Hirst D (British Journal of Learning Disabilities, 2002)
Summary It is argued that challenging behaviours can be better understood if a correlational analysis (i.e. looking for correlations between the occurrence of the behaviour and other variables) is used in addition to functional analysis. A case example is provided of a man whose aggressive outbursts were negatively correlated with trips out of his unit.